The sculpture of tick-borne diseases media coverage in the United States and China - Tang, Yanzhe (2017)
Media’s ability to enhance the salience of certain topics for the public and affect governmental policy-setting processes is widely recognized.  This is particularly evident in health communication, where newspapers are one of the most important sources of health information. This study compares media depictions of tick-borne disease in the United States and China, attempting to enhance newspaper influence in health information delivery in both countries. The United States and China are experiencing an increase in tick-borne diseases and have vastly different media landscapes.  To investigate US and Chinese newspaper coverage of tick-borne diseases, a content analysis was conducted of four US and four Chinese newspapers.  The analysis considered length, tone, chief actors, and themes present in articles covering tick-borne diseases from January 2010 to August 2015.  The findings revealed significant differences between the two nations on length of the articles, chief actors portrayed in the articles, and themes present in the articles. According to Agenda setting theory, media to public communication is not one way, on the contrary, public react to the media and media coverage reflects public preferences. The data showed that tick-borne disease stories were overwhelmingly framed in a neutral way in both nations; newspapers in the US featured more celebrity-related stories compared to newspapers in China; and Chinese government controlled newspapers as opposed to the US ones have leading impact to their domestic newspapers. Generally, to shape public health behavior and reduce tick-borne disease risk, the US newspapers can frame more celebrity related stories in the report and Chinese government owned newspaper can take the initiative to cover more tick-borne disease news.